Morphological modifications induced by an artificial diet on the hypopharyngeal glands of Apis mellifera (Hymenoptera, apidae) during their degenerative process - Furquim, KCS [UNESP]; Camargo-Mathias, M. I. [UNESP]; de Moraes, RLMS [UNESP] (California State University, 2004)
The morphological aspects of the hypopharyngeal glands were analyzed in worker bees of Apis mellifera of 15 and 30 days of age. The individuals were kept in a room with controlled temperature at 32degreesC where they received water and either a protein or a high energy food. Nurse and foraging workers were used as a control for the experiment. The morphological results showed that the different diets modified the cell death characteristics and intensified its occurrence. Both diets caused precocious glandular degeneration. However, this anticipation of cell death was more pronounced in the glandular tissue of the workers who received the high energy diet when compared to the glands of the bees fed with the protein meal.The degenerative signs observed were an intense cytoplasmic vacuolization, with a loss of cytoplasm and of the cell boundaries, dilation or condensation of the cells and nuclei, and nuclear fragmentation. At the end of the degenerative process, we observed the extrusion of nuclei and, finally, the dissolution of the glands. The hypopharyngeal glands' remains were found in the haemolymph.
Keywords: Apis mellifera; hypopharyngeal gland; cell death; artificial diet